A review on COVID-19 vaccines: stages of clinical trials, mode of actions and efficacy. Issue 1 (1st January 2021) - Zahid, Muhammad Nauman; Moosa, Mustafa Shehab; Perna, Simone; Buti, Ebtisam Bin
Abstract: Coronavirus disease (COVID-19) is a communicable disease caused by a recently discovered coronavirus. The disease was first reported in Wuhan, China at the end of 2019 and has resulted in 1.71 million global deaths and over 77 million infections. Common symptoms of the disease include fever, dry cough, and fatigue. This literature review aims to summarize the following topics: review the clinical trials conducted on nine COVID-19 vaccines and follow their efficacy and modes of action through the three stages of the vaccine clinical development process. The analysis follows the individual vaccines through the three trials, examining and analysing drawn results to identify their capacity to contain severe acute respiratory syndrome (SARS-CoV-2). Four COVID-19 vaccines have been approved for use in different parts of the world and many other vaccines are under clinical trials 1, 2 and 3. In conclusion, these vaccines which are under clinical trials provide a great hope to fight against COVID-19 in near future.